Effect of processing on the concentrations of boar taint compounds skatole and androstenone in different types of sausage. Issue 4 (25th January 2018) - Marro, Philipp; Bauer, Aneka; Stefanski, Volker; Weiler, Ulrike
Abstract: In order to valorize tainted meat from entire male pigs, two options exist in the production of different meat products: either to dilute tainted meat or to mask off‐odors in the final product. Processing steps may also reduce the concentrations of boar taint compounds. This study investigated the impact of different processing methods on the concentrations of boar taint compounds skatole and androstenone in meat products. Three different types of German sausages, such as raw fermented (salami), boiled (wiener), and cooked meat sausages (liver sausage), were produced from boar meat and fat with either "high" or "low" taint level. Heating during processing, especially the production of wiener and liver sausage, reduced androstenone concentrations between 44 and 87%. In salami, androstenone concentrations were not reduced during production process. In contrast, skatole reductions of up to 26% were observed for salami and up to 44% for wiener, whereas liver sausage was not affected. Practical applications: The risk of offensive boar taint is one of the main disadvantages of pork production with entire males. If the detection of tainted carcasses at the slaughter line can be improved, a valid strategy to valorize such carcasses is crucial. The study revealed that open heating during processing has the potential to reduce androstenone, whereas smoking of the products seems to reduce skatole concentrations in the final product.